The Decline in Task Performance After Witnessing Rudeness Is Moderated by Emotional Empathy—A Pilot Study - Gilam, Gadi; Horing, Bar; Sivan, Ronny; Weinman, Noam; Mackey, Sean C. (Frontiers in Psychology, 2020)
Rude behaviors engulf societies across the world on a daily basis. Witnessing rudeness towards others increases negative affect and decreases performance in various tasks requiring behavioral and cognitive efforts, such as solving word puzzles or creative and flexible thinking. In this pilot study we examined whether different levels of emotional empathy that may influence susceptibility to others’ distress, moderated the declined performance in several such tasks. The study was conducted on-line as a naturalistic setting for witnessing movie-clips portraying rudeness. We hypothesized that all participants will demonstrate decreased task performance following a rude compared to a neutral condition, but more so for those higher on emotional empathy. Results confirmed each of these hypotheses in one of two different cognitive tasks. Findings suggest that after witnessing rudeness, those higher on emotional empathy perform worse in cognitive tasks. While requiring replication in a larger sample size, empathic processing seems to be a potential moderator of the effect of rudeness on task performance.